Occurrence of Terrifying Nightmares after Few Days of Mirtazapine Use in Elderly Patients - Dell’Osso, Liliana; Lorenzi, Primo; Nardi, Benedetta; Carpita, Barbara; Benedetti, Francesca; Cremone, Ivan Mirko (Case Reports in Psychiatry, 2023)
Introduction. Sleep disturbance and insomnia are some of the most frequent complaints in patients suffering from depression. Some common antidepressant with excitatory effects may worsen sleep qualities, whereas others (like mirtazapine), thanks to their antihistaminergic action, are associated with sedative properties and can quickly improve sleep quality. In the case of mirtazapine, even if its mechanisms of action on sleep remain controversial, beneficial changes in sleep pattern may be observable since the first dose and are associated with a faster onset of the antidepressive action. Case Presentation. Despite these documented beneficial effects, we reported five cases of elderly patients (age ranging from 69 to 79) with various diagnoses and comorbidities (severe or recurrent depression, general anxiety disorder, borderline personality disorder, and Parkinson’s disease) assessed during clinical daily routine for whom the use of mirtazapine was linked to the onset of nightmares so impressive and dramatic that made it necessary to interrupt the treatment. Discussion. This peculiar side effect is still scarcely documented, and the literature on this topic remains conflicting; however, considering that the cases were collected in a short range of time, the exacerbation of nightmares caused by mirtazapine may be more frequent than previously believed. Furthermore, some common features shared by all the cases reported have been highlighted such as the onset of the nightmares being chronologically associated with the initiation of the therapy with mirtazapine, the disappearance with the interruption, the similar age range of all, and the occurrence of the episodes described during fall season.